2018
DOI: 10.1002/jor.24176
|View full text |Cite
|
Sign up to set email alerts
|

Variations in contents of hyaluronan in the peritumoral micro‐environment of human chondrosarcoma

Abstract: A concept consolidated in recent years is that tumor growth depends to a great extent on the micro-environment surrounding the tumor, which has a fundamental role in tumor progression and in determining the effectiveness of therapies. Our analysis focuses on chondrosarcoma, the second primary malignant bone tumor, resistant to both chemotherapeutic and radiation therapy. We quantified hyaluronan, one of the main components of the extracellular matrix, with the aim of comparing its amount in the connective tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Despite several novel therapeutic approaches, surgery is still undisputedly the cornerstone in the treatment of chondrosarcoma, as chemotherapy and radiation therapy are not effective, due to the poor vascularity, extracellular matrix, and the low percentage of dividing cells (3,16,18). In other histotypes that could affect the thoracic cage, such as breast cancer, radiation therapy represents a significant local adjuvant after radical surgery (19).…”
Section: Figure 3 Kaplan-meier Curves Show the Overall Survival Of Patients Who Presented At Our Institutions With A Primary Chondrosarcomentioning
confidence: 99%
“…Despite several novel therapeutic approaches, surgery is still undisputedly the cornerstone in the treatment of chondrosarcoma, as chemotherapy and radiation therapy are not effective, due to the poor vascularity, extracellular matrix, and the low percentage of dividing cells (3,16,18). In other histotypes that could affect the thoracic cage, such as breast cancer, radiation therapy represents a significant local adjuvant after radical surgery (19).…”
Section: Figure 3 Kaplan-meier Curves Show the Overall Survival Of Patients Who Presented At Our Institutions With A Primary Chondrosarcomentioning
confidence: 99%
“…Many reports show that an increase in HA levels in tumor ECM correlates with tumor progression of different type of cancer, as carcinoma, sarcoma, ect. [ 45 , 49 ]. The loss or decrease of HYAL1 was proposed as one of the reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In virtue of its tendency to aggregate, hyaluronan forms supramolecular complexes that contribute to the pericellular matrix organization [ 30 ]. By comparing hyaluronan content in ChS tissues with normal chondroid tissue as a control, Fede C. and colleagues found that a correlation exists between hyaluronan content, ChS aggressiveness, and chemoresistance [ 51 ]. Accordingly, the 4-methylumbellifer that is an inhibitor of hyaluronan synthesis prevents ECM formation, reducing in vitro and in vivo proliferation and invasion of rat ChS cells [ 52 ].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%